The Effect of Work Culture on Teacher Performance Through Citizen Organizational Behavior and Work Engagement as Mediating Variables - Vianey Nara Uran, Alfonsus; Subiyanto, Didik; Hadi, Syamsul (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The specific problem faced in this context is how work culture in public school institutions in East Flores Regency affects teacher performance through the mediating variables of Organizational Citizenship Behavior (OCB) and Work Engagement. This research uses quantitative methods with a survey approach. The research design used was a survey design, where data were collected using questionnaires distributed to the entire population of teachers in public high schools in East Flores Regency totaling 100 teachers. The results showed that work culture has a positive effect on Organizational Citizenship Behavior (OCB) and work engagement which further improves teacher performance, although work engagement has no direct effect on performance. In addition, OCB proved to be a significant mediator in the relationship between work culture and teacher performance. Based on the results of the discussion, it can be concluded that work culture is proven to have a positive influence on Organizational Citizenship Behavior (OCB), work engagement, and teacher performance. SmartPLS analysis shows that OCB work culture has an estimated value of 0.678 and a t-statistic value of 11.923 (p-value 0.000), for work engagement with an estimated value of 0.610 and a t-statistic of 11.186 (p-value 0.000), and for teacher performance with an estimated value of 0.220 and a t-statistic of 1.977 (p-value 0.049).